Early Postnatal Care Utilization and Associated Factors Among Women Who Give Birth in the Last Six Weeks in Hosanna Town, Southern Ethiopia, 2022 - Sintayehu Worku; Merga Dheresa; Tilahun Ali; Mengistu Lodebo (Journal of Pregnancy)
Conclusion: In comparison to World Health Organization standards, the study’s overall prevalence of early postnatal care utilization was low. Early postnatal care use was significantly associated with antenatal care follow-up, the husband’s educational level, knowledge of early postnatal care use, and length of stay at the health institution following birth. As a result, the strength of health facilities is to improve service provision, information education, and communication.